Application of Fuzzy Logic for Android-Based Tempeh Fermentation Process Control and Monitoring - Isac Ilham Akbar Habibi; Septriandi Wirayoga; Miftakhul Huda; Guntur Yanuar Astono (Jurnal Indonesia Sosial Teknologi, 2024)
Tempeh is a highly nutritious food source that is widely consumed by people every day. Tempeh artisans, such as those in Jatisari Village, produce quality tempeh through an optimal fermentation process. The ideal fermentation process takes place at a temperature of 30°C–35°C, a humidity of 65%–72%, and an ammonia gas content of 43–50 ppm, with a fermentation time of about 18 hours to produce cooked tempeh. To improve the efficiency and quality of the fermentation process, a tool that is able to control and monitor the condition of the fermentation chamber is needed automatically. This research develops a tempeh fermentation control and monitoring system using a NodeMCU microcontroller, relay, VNH2SP30, DHT11 sensor, and MQ-137 sensor, which are integrated with fuzzy logic. This system controls the incandescent lamp as a heater and the peltier as a cooler in the fermentation container compartment. Control and monitoring results are displayed in real-time via LCD and Android app, with the successful fermentation time shortened to 16 hours.